1982
DOI: 10.3171/jns.1982.57.5.0609
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury, spinal fracture, and spinal stenosis in ankylosing spondylitis

Abstract: The authors report a retrospective review of 105 patients with ankylosing spondylitis (AS) diagnosed over a 6-year period in Tucson, Arizona. In the series, there were 13 patients with spinal fractures and eight with severe spinal cord injury. Two patients with central cord contusion had no demonstrable cervical spine fracture. Injury was often trivial and dislocation at fractures sites was minimal, demonstrating the extreme fragility of these patients. Spinal stenosis, which has not previously been associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
90
0
10

Year Published

1983
1983
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 24 publications
1
90
0
10
Order By: Relevance
“…Wilkinson and Bywaters (1958) noted two patients with lumbar fracture in a review of 222 AS patients who were followed for from one to 20 years (mean, 4.6 years). Weinstein et al (1982), in their study of 105 consecutive cases of AS, noticed that the frequency of spinal fracture was 12 per cent and the frequency of myelopathy was 8 per cent. In our study, the incidence of cervical cord injury in AS patients was 1.5 per cent over a period of 12 years.…”
Section: Discussionmentioning
confidence: 97%
“…Wilkinson and Bywaters (1958) noted two patients with lumbar fracture in a review of 222 AS patients who were followed for from one to 20 years (mean, 4.6 years). Weinstein et al (1982), in their study of 105 consecutive cases of AS, noticed that the frequency of spinal fracture was 12 per cent and the frequency of myelopathy was 8 per cent. In our study, the incidence of cervical cord injury in AS patients was 1.5 per cent over a period of 12 years.…”
Section: Discussionmentioning
confidence: 97%
“…Prompt rigid immobilization by either surgical or external means is required. 10,11 The consequence of delayed diagnosis of a spinal fracture in this population of patients is illustrated in two series by Trent et al and Broom and Raycroft. In the former, six of seven cases had diagnoses missed on initial examination and two of these developed a complete paraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…6 Weinstein et al stated that AS patients with spinal pain should be handled carefully during transfer and transport because of the risk of fracture or dislocation at a previous fracture site. 16 The second SCI in our patient was at T9, and was clearly detected as cord infarction on MRI performed in the second month after injury. The absence of any bone lesion and/or hematoma at that level on both CT and MRI indicated that the problem was vascular insu ciency.…”
Section: Discussionmentioning
confidence: 59%
“…2 ± 4 Another characteristic feature of spinal lesions in AS patients is discovertebral destruction or pseudoarthrosis, as was seen in our patient, in which the development of ®brous connective tissue at the site of fracture results in mobile nonunion. 2,5,15,16 It is suggested that the radiological appearance of pseudoarthrosis can be very similar to discovertebral infection, and recognition of this entity in AS patients may eliminate the need for needle biopsy or surgical exploration. 16 On MRI we detected severe bone destruction, and soft tissue component causing marked spinal stenosis in our patient at L2,3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation